Infraestructura tecnológica y gestión administrativa en la municipalidad distrital de Yauli 2021 - Paco Huamani, Wilfredo Fredy (2023)
The research focuses on analyzing the relationship that exists between technological infrastructure and administrative management in the District municipality of Yauli 2021, where the importance of the use of ICTs is taken. The use of ICTs in the entire sphere, both private and public, has been expanded since, in this way, the efficiency of the process, information treatment, is improved, so improving the technological infrastructure can positively impact the administrative management of local governments. . The study is a basic type of correlational level, with a non-experimental cross-sectional design, where the Likert scale was used as an instrument, for the evaluation of 28 public servants, the results shown is that there is a normal distribution of the two variables, where it is found that there is a positive correlation of 0.447.